Contrast enhancement of chronic subdural hematomas after embolization of the middle meningeal artery. Issue 5 (October 2019) - Entezami, Pouya; Boulos, Alan; Paul, Alexandra; Nourollahzadeh, Emad; Dalfino, John
Chronic subdural hematomas are a common neurosurgical presentation. They are difficult to treat, and current interventions – namely surgical evacuation – are not without complications or recurrences. Embolization of the middle meningeal artery is a promising new treatment option for this pathology. We have noted an interesting phenomenon in our patients following endovascular embolization, which is that the subdural hematoma is stained with contrast following the procedure. This ties into the basic physiology of chronic subdurals, which parasitize the middle meningeal artery during the process of membrane formation and neovascularization, which has previously been reported.